Cigarette Demand, Taxation, and the Poor : A Case Study of Bulgaria - Sayginsoy, Ozgen; Yurekli, Ayda A.; de Beyer, Joy (World Bank, Washington, DC, 2013)
This paper uses data from the Living Standards Measurement Study (LSMS) Household Survey conducted in 1995, to analyze demand for manufactured cigarettes in Bulgaria and the effects on the poor of a hypothetical revenue-maximizing specific excise tax increase on cigarettes. A cigarette tax increase is the single most effective and cost-efficient measure to reduce smoking. The first objective of this paper is to estimate the price and income of consumption for cigarettes in Bulgaria by income groups. The second objective is to simulate the impact of changes in specific excise taxes on consumption, tax burdens and government revenues from cigarette taxes. A major concern among policymakers is that an increase in cigarette taxes could have a disproportionate impact on the poor.